Orientacja rynkowa w dobrym współrządzeniu miastem w perspektywie urzędników samorządowych - Anders-Morawska, Justyna (Polityka i Społeczeństwo, 2020)
The scope of the paper is to analyse the model of public governance by the application of the concept of market orientation. The author posits a new approach in resolving the problem of the assessment and evaluation of territorial government practices in the area of urban governance. The research was carried out in 8 large Polish cities and concentrated on the processes with regards to the improvement of the attractiveness of the city for external users such as: investors, tourists and potential students. The competitive nature of these processes as well as the necessity to take concerted actions with non-governmental and private partners set boundaries for a simultaneous analysis of market orientation on the one hand and collaborative governance on the other. The process of data collection comprised content analysis, in-depth interviews, an on-line survey and the mystery client method. Based on information acquired during research process the author assumes local administration to follow a middle path between two models of public management: new public management and new public governance with the aforementioned in the ascendency. The components of market orientation were visible in managerial practices of the cities concerned: public managers acknowledge the necessity to acquire intelligence with regard to users’ needs, undertake activities in order to coordinate efforts in the area of satisfying these needs, and attempts to monitor the results of these actions.